Structural Design and Analysis of Adaptive Pipe Diameter Full Drive Pipeline Robots - Zheng Likang; Feng Yongli; Li Zhanxian; Liu Zhenhua (Jixie chuandong)
Aiming at the problem that the internal condition of the pipeline can not pass the manual inspection after the completion of welding, a pipeline robot which can independently inspect the welded pipeline is proposed. The robot can adapt to the change of pipe diameter autonomously, so as to solve the problems of complicated control and low control precision caused by the artificial control of the support mechanism. Firstly, the design requirements of the pipeline robot are presented, and the overall structure and working principles of the pipeline robot are introduced. Secondly, the scheme design and force analysis of the supporting mechanism of the robot are carried out, and the geometric constraints of the overall structure of the pipeline robot and the movement constraints in the bend are analyzed. Finally, Adams software is used to simulate the proposed scheme to verify its passability in the pipeline.